Parental Reflective Functioning and Object Relations in Adolescents: A Path Model of the Direct and Indirect Effects on Reactive Aggression through Mentalization - Abbasi, Hanieh; Jafari, Afnan; Khalednejad, Mona; Khalatbari, Javad; Hosseini , Fakhri Sadat (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to investigate the direct and indirect effects of parental reflective functioning and object relations on reactive aggression among adolescents through the mediating role of mentalization. Methods and Materials: This study employed a descriptive-correlational design based on path analysis. The statistical population included adolescents enrolled in the second cycle of secondary education (grades 10–12) during the 2025–2026 academic year. Participants were selected using a multistage cluster sampling method, and after screening incomplete responses, the final sample consisted of 463 adolescents aged 15–18 years. Data were collected using the Parental Reflective Functioning Questionnaire–Adolescent Version (PRFQ-A), Bell Object Relations and Reality Testing Inventory (BORRTI), Reflective Functioning Questionnaire for Youth (RFQY), and Reactive–Proactive Aggression Questionnaire (RPQ). Data analysis was performed using SPSS version 27 and AMOS version 26. Descriptive statistics, Pearson correlation analysis, and path analysis with bootstrap estimation were used to examine direct and indirect relationships among variables. Findings: The results showed that parental reflective functioning significantly and positively predicted mentalization (β = 0.389, p < .001), and object relations also had a significant positive effect on mentalization (β = 0.208, p < .001). Mentalization significantly and negatively predicted reactive aggression (β = -0.447, p < .001). Furthermore, parental reflective functioning (β = -0.145, p < .001) and object relations (β = -0.183, p < .001) had significant direct negative effects on reactive aggression. Bootstrap analysis confirmed the significant mediating role of mentalization in the relationship between parental reflective functioning and reactive aggression (indirect effect = -0.174, 95% CI [-0.224, -0.129]) and between object relations and reactive aggression (indirect effect = -0.093, 95% CI [-0.140, -0.051]). The final model explained 38.5% of the variance in reactive aggression. Conclusion: The findings highlight the importance of parental reflective functioning and adaptive object relations in reducing adolescents’ reactive aggression by strengthening mentalization capacities.